Inhibitory effect of oral thin films (OTFs) containing xylitol against streptococcus mutans / Elizabeth Teng Yi Ern, Hee Xixian and Muhamad Fareez Ismail - Yi Ern, Elizabeth Teng; Xixian, Hee; Ismail, Muhamad Fareez (Universiti Teknologi MARA, 2022)
Dental Caries is a chronic disease affecting half of the global population, causing pain and discomfort due to progressive damage to the teeth. Whilst xylitol has been studied for its effect on dental caries prevention, current practices present few limitations for its successful oral delivery, including short residence time in the mouth and poor patient compliance. Recently, oral thin films (OTFs) emerged as an alternative to delivering xylitol in the oral cavity. This research aims to develop novel OTFs containing xylitol with extended-release properties (as determined by the disintegration time) and to investigate its effect on a cariogenic bacterial strain, Streptococcus mutans. The minimum inhibitory concentration (MIC) of xylitol was determined. Employing the microdilution broth method, the antibacterial activity of the oral thin films containing xylitol for oral S. mutans was performed with simulated salivary fluid, incubated at 1, 4, and 10 h. The MIC of xylitol was found at 10%. Meanwhile, there was no significant difference in the inhibition of S. mutans (p > 0.05) between the control, OTFs (10 h), and xylitol-OTF (1 h), with the latter, demonstrated only 16.58% inhibition. Interestingly, when compared to xylitol-OTF (1 h), xylitol-OTF showed significant inhibition (p < 0.05) to S. mutans after four h (+53.24 %) and almost a complete inhibition after ten h (-92.58 %). These results suggest that the OTFs demonstrated a gradual release of xylitol and inhibited oral biofilm formation by decreasing the growth of S. mutans in a time-dependent manner. Most importantly, the study indicated the successful development of a novel xylitol-OTF with potential as an oral health biotherapeutic agent.